Software “slide” for sprinkle irrigation lateral line design - Andrini, Marcelo [UNESP] (2019)
Sizing conventional downhill sprinkler lateral lines requires careful consideration, as the pressure distribution profile along the line can take different configurations depending on the slope of the terrain. The objective of this work was to develop a software, called SLIDE, that allows to interactively design of the lateral lines in any slope condition, including downhill. The computer program was developed in Microsoft Excel-2016, has an intuitive interface, with tablet-shaped output data containing the hydraulic performance of the lateral line and easy-to-interpret graph, which dynamically adjusts according to the type of profile. Three case studies were presented and solved. Interactively, SLIDE software has made it possible to design lateral lines of conventional sprinkler irrigation systems properly, especially in the sloping condition.